INCOMING AND OUTGOING LETTER SERVICE FOR THE ACADEMIC SECTION OF LAMBUNG MANGKURAT UNIVERSITY - Noor Razikin; Sitti Rahmawati (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
Letter services in the academic section of Lambung Mangkurat University include students and alumni. The manual correspondence system, i.e. the proposer of letters must come directly to the Academic Section, becomes an obstacle for students and alumni who are out of town. From these obstacles, the solution is in the form of building a mailing service information system in the website-based academic section that can assist in the service of the letter. The analytical method used is the PIECES method, which is the analytical method as the basis for obtaining more specific issues. The analysis is described by discussing UML to stakeholders. The design uses Laravel with MySQL MariaDB database. The website is designed with 10 tables with 3 user levels, namely proposer, coordinator, and leader. Testing this system using Black Box with 49 test scenarios. The results of the design of the academic section of the correspondence website can be built. Blackbox testing gives 100% results according to all functions on the academic letter service website.